Maleagi 1:9 - 'n crux interpretum - S. D. Snyman (Acta Theologica)
Malachi 1:9 presents the interpreter or exegete with unexpected difficulties. A number of these difficulties are treated in this article: problems pertaining to the translation of the text in Afrikaans, text-critical problems, the problem of the identity of the speaker(s); the question of whether the text should be interpreted as ironic or not. The investigation resulted in the following: The weaknesses of current translations of the text are pointed out and a new translation in Afrikaans is proposed. Text-critical questions are treated and it is found that there is no compelling reason to alter the text. The speaker is identified as the prophet and not the priests or the people. Finally, it is indicated that there is no need to understand the text ironically; it is rather a serious appeal by the prophet directed to the priests.